1999
DOI: 10.1088/0953-4075/32/19/316
|View full text |Cite
|
Sign up to set email alerts
|

The angle-resolved Kr L2,3M4,5M4,5Auger multiplet following proton impact ionization

Abstract: The angle-resolved Kr L2,3M4,5M4,5 Auger spectra induced by proton impact ionization were measured at 1, 2.6 and 3.6 MeV proton energies where high-resolution spectroscopy techniques have been applied. The Auger energies and relative line intensities are compared with different earlier experimental data as well as our numerical results which have been obtained within a multiconfigurational Dirac-Fock approach. The alignment parameter 20 of the singly ionized krypton atoms has been extracted from the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The observation of the 1 G 4 decay in the present study has shown that the angular distribution is close to isotropic; the absolute value of the anisotropy parameter is lower than 0.1. A previous calculation predicts that the parameter is -0.045 [22].…”
Section: Assignment Of the Resonant Auger Peaksmentioning
confidence: 93%
See 2 more Smart Citations
“…The observation of the 1 G 4 decay in the present study has shown that the angular distribution is close to isotropic; the absolute value of the anisotropy parameter is lower than 0.1. A previous calculation predicts that the parameter is -0.045 [22].…”
Section: Assignment Of the Resonant Auger Peaksmentioning
confidence: 93%
“…In addition, in the energy range of interest the normal Auger peaks are distorted through the post-collision interaction (PCI), and these peaks can be approximated with the following equation [10,22,[33][34][35][36]:…”
Section: Peak-fitting Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kr:LMM normal Auger spectra following photoionization were also observed for the first time in this study and will be reported in detail elsewhere. Spectra following electron and proton impact ionization in the vapour phase (Krause 1965, Siegbahn et al 1969, Werme et al 1972, Aksela et al 1980, Levin et al 1986, Kleiman et al 1999 and in solid samples (Baba et al 1992, Marton et al 1993 were reported previously. Baba et al (1992) used an aluminium-Kα line source (1486 eV), and thus their assignment is questionable.…”
mentioning
confidence: 87%
“…The Kr:2p electron can be photoexcited into the 5s orbital (Wuilleumier 1971, Schmelz et al 1995, but there is no report of electron emission associated with Auger transitions from the Kr:2p −1 5s state. Further, although normal Auger electron spectra from Kr:2p −1 states were measured following electron-beam and proton-beam excitation (Krause 1965, Siegbahn et al 1969, Werme et al 1972, Aksela et al 1980, Levin et al 1986, Kleiman et al 1999, normal Auger electron emission from Kr:2p −1 states using x-ray excitation has not yet been studied in the vapour phase. The lack of data for the Kr:2p −1 state may be due to the difficulty of using a bright photon source that can supply, with a high resolution, photons of about 1700 eV, required to produce the Kr:2p −1 states.…”
mentioning
confidence: 99%